Pelatihan English for Library Guiding Service sebagai Upaya Peningkatan Kualitas Layanan Balaiyanpus DPAD DIY - Nurhayati, Ari; Kurnia, Nandy Intan; Anggraeni, Niken (Jurnal SOLMA, 2025)
Background: The demand for professionalism at work obliges librarians to have skills, not only related to library management but also foreign language mastery, especially English as an international language. One of library programs that need language mastery is library guiding service or library tours, which provides services by guiding library guests including those from foreign countries. To succeed the program, English mastery is undeniably useful to communicate with foreigners. Thus, the English Literature Study Program UNY conducted a community service program to improve the librarians’ English skills to serve international guests, which in itself will improve their quality, both locally and internationally. Methods: Workshop by providing several materials, namely Dealing with Guests, Giving Direction, Giving Information on Collections and Services, and role play which showcased the English language skills of the participants. Results: High score of the participants’ satisfaction related to the topic of workshop, materials, teaching method, communication, media, punctuality, and benefits, shows the relevance between the participants’ needs and the PKM team. Conclusions: Based on the evaluation results, the participants hoped that similar activities could be carried out regularly because the participants could feel the benefits directly.